2021
DOI: 10.18485/aeletters.2021.6.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Industrial Fan System Using Methods Laser Alignment

Abstract: The research in this paper aimed to show the importance of axial alignment on the example of maintaining a technical system. In this paper, the importance of alignment is examined on industrial fans. The technical system on which the alignment was performed reached the anticipated bearing life of 23,650 operating hours prescribed by the manufacturer, while the technical system on which the alignment was not performed was exposed to excessive load by a misalignment shaft. As a result, it did not meet the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Da bi se sprovelo proaktivno održavanje, kojem ovaj koncept pripada, prognoza budućeg stanja sistema mora integrisati maksimum dostupnih informacija kako bi donela zaključak o stanju sistema što je realističnije moguće [6]. Detekcija kvarova i identifikacija vrste kvara su veoma važni kako bi se osigurala bezbednost mašine i kvalitet proizvodnje [7][8][9].…”
Section: Uvodunclassified
“…Da bi se sprovelo proaktivno održavanje, kojem ovaj koncept pripada, prognoza budućeg stanja sistema mora integrisati maksimum dostupnih informacija kako bi donela zaključak o stanju sistema što je realističnije moguće [6]. Detekcija kvarova i identifikacija vrste kvara su veoma važni kako bi se osigurala bezbednost mašine i kvalitet proizvodnje [7][8][9].…”
Section: Uvodunclassified
“…Eleonora et al [28] explored roller bearing diagnostics, enhancing selection and maintenance strategies. Borivoj et al [29] demonstrated that laser alignment and vibro-diagnostics on industrial fans can quadruple bearing life, contrasting sharply with the early failures of misaligned systems. These studies collectively advance the field of preventive maintenance, highlighting its importance in enhancing production equipment safety and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Rolling bearings represent the most common case of such rolling elements failure in the piston air compressor [9]. The values which are inherent characteristics of the normal bearing operating system are conditioned not only by the system project design, manner of its development and operation, but also by the alteration of environmental conditions as well [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%